Nitrogen deposition in Mediterranean forests. - Roda, F.; Avila, a; Rodrigo, A. (Environmental pollution (Barking, Essex : 1987), 2002)
Atmospheric deposition of inorganic nitrogen was studied at two forested sites in the Montseny mountains (northeast Spain), peripheral to the Barcelona conurbation, and at a nearby lowland town, using bulk deposition, wet-only deposition, throughfall, and dry deposition inferred from branch-washes and surrogate surfaces (metacrylate plates). Bulk deposition inputs of ammonium and nitrate did not show significant temporal trends over a 16-year period. Bulk inputs of inorganic N were moderate, ranging from 6 to 10 kg N ha(-1) year(-1) depending on the time period considered and the degree of site exposure to polluted air masses from the Barcelona conurbation. Large dry-sedimented particles played a minor role, since wet-only inputs were virtually identical to bulk inputs. On the contrary, branch- and plate-washes indicated substantial dry inputs of N gases and small particles. Total atmospheric deposition was estimated at 15-22 kg N ha(-1) year(-1), most of it being retained within the studied broadleaved evergreen forests. Ecosystem N availability is thus likely to be increasing in these forests.
The following values have no corresponding Zotero field: accession-num: 11939283
Keywords: Air Pollutants; Air Pollutants: analysis; Biological Availability; Ecosystem; Environmental Monitoring; Gases; Geologic Sediments; Geologic Sediments: chemistry; Mediterranean Region; nitrogen; Nitrogen: analysis; Particle Size; Trees; Trees (citation)

Nitrogen deposition in Mediterranean forests. - Rodà, F; Avila, a; Rodrigo, a (Environmental pollution (Barking, Essex : 1987), 2002)
Atmospheric deposition of inorganic nitrogen was studied at two forested sites in the Montseny mountains (northeast Spain), peripheral to the Barcelona conurbation, and at a nearby lowland town, using bulk deposition, wet-only deposition, throughfall, and dry deposition inferred from branch-washes and surrogate surfaces (metacrylate plates). Bulk deposition inputs of ammonium and nitrate did not show significant temporal trends over a 16-year period. Bulk inputs of inorganic N were moderate, ranging from 6 to 10 kg N ha(-1) year(-1) depending on the time period considered and the degree of site exposure to polluted air masses from the Barcelona conurbation. Large dry-sedimented particles played a minor role, since wet-only inputs were virtually identical to bulk inputs. On the contrary, branch- and plate-washes indicated substantial dry inputs of N gases and small particles. Total atmospheric deposition was estimated at 15-22 kg N ha(-1) year(-1), most of it being retained within the studied broadleaved evergreen forests. Ecosystem N availability is thus likely to be increasing in these forests.
Keywords: Air Pollutants; Air Pollutants: analysis; Biological Availability; Ecosystem; Environmental Monitoring; Gases; Geologic Sediments; Geologic Sediments: chemistry; Mediterranean Region; nitrogen; Nitrogen: analysis; Particle Size; Trees; Trees (citation)

Pyrolysis of holm-oak wood: influence of temperature and particle size - Figueiredo, J L; Valenzuela, C; Bernalte, A; Encinar, J M (Fuel, 1989)
The pyrolysis of holm-oak wood sawdust was studied to determine the characteristics of the charcoal and the nature and amounts of gases produced. The temperature was varied from 300 to 900 °C and the wood particle size from 0.40 to 2 mm diameter. The fixed carbon content of the charcoal increased with temperature up to 700 °C, and then remained essentially constant. The gases produced were mainly CO, CO2, H2 and CH4. The rate constants and activation energies for the production of each gas were calculated assuming first order kinetics. The composition of the pyrolysis gas produced at each temperature was determined, and its heating value was calculated. Taking into consideration the quality of the charcoal and the heating value of the gases produced, it can be concluded that the optimal pyrolysis temperature is ≈ 600 °C.
Keywords: charcoal; Particle Size; pyrolysis

Pyrolysis of holm-oak wood: influence of temperature and particle size - Figueiredo, J. L.; Valenzuela, C.; Bernalte, A.; Encinar, J. M. (Fuel, 1989)
The pyrolysis of holm-oak wood sawdust was studied to determine the characteristics of the charcoal and the nature and amounts of gases produced. The temperature was varied from 300 to 900 °C and the wood particle size from 0.40 to 2 mm diameter. The fixed carbon content of the charcoal increased with temperature up to 700 °C, and then remained essentially constant. The gases produced were mainly CO, CO2, H2 and CH4. The rate constants and activation energies for the production of each gas were calculated assuming first order kinetics. The composition of the pyrolysis gas produced at each temperature was determined, and its heating value was calculated. Taking into consideration the quality of the charcoal and the heating value of the gases produced, it can be concluded that the optimal pyrolysis temperature is ≈ 600 °C.
Keywords: charcoal; Particle Size; pyrolysis